Gender Representation in Indonesian EFL Coursebook for 12th Grade - Noviyanti, Sari Dewi (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
Gender representation in educational materials is a crucial aspect of fostering inclusivity and promoting social equity in the classroom. Ensuring accurate and equitable gender representation is needed to foster inclusive learning environments. This article presents the findings of a study which analyzed the gender representation within the latest English coursebook for senior high school students which adapt Kurikulum Merdeka and published by Indonesian Ministry of Education, Culture, Research and Technology. The data for this research extracted from reading passages and images in the English coursebook titled